Evaluation of preschool children's fantasy play in the tabletop environment - Mansor, Evi Indriasari
This paper presents the experience and findings of a user study investigating preschool children's fantasy play. Ten same-sex dyads of children (aged 3 and 4) were observed playing with the physical farm toys and the virtual farm set implementation on a Mitsubishi DT multi-touch interactive tabletop. Both qualitative and quantitative data were performed for data collection. Findings showed that high evidence of fantasy play bouts performed by the participants during the physical and the virtual Session 2. This paper also reports the similarities and differences between physical and virtual play environments.